Parent-Child Concordance and Discordance in Family Violence Reporting: A Descriptive Analysis from the Adolescent Brain Cognitive Development Study® - Hogan, Jasara N. (Journal of interpersonal violence, 2023)
Childhood trauma exposure, including witnessing or experiencing family violence, is associated with a variety of poor outcomes such as increased likelihood of psychopathology and high-risk behaviors across the lifespan. Early treatment may help to buffer these effects, but parents and youth display only moderate levels of agreement in reporting family violence, making it more difficult to identify children who have been exposed. Additionally, most studies on family violence reporting have focused primarily on small samples in specific high-risk populations, and little is known about the generalizability of these findings. Thus, the present study assessed concordance in family violence reporting and its correlates using the population-based, demographically diverse sample from the U.S. Adolescent Brain Cognitive Development (ABCD®) study. Participants were 10,532 children between 9 and 10 years old, and their parent or guardian, from 21 sites across the United States. Overall, 30% (N = 3119) of the sample reported family violence and most of those reports (N = 2629) had discordant violence reporting, meaning child- and parent-report did not correspond with each other. Multinomial logistic regression was used to assess the likelihood of participants belonging in one of the following groups: no violence reported, concordant violence reported, and discordant violence reported. Results indicated that Black or Non-Hispanic children, male children, and children with greater externalizing problems were more likely to report family violence, and parents with lower levels of education and income were more likely to report family violence. These findings likely reflect differences in distribution of risk factors among racial and ethnic minoritized individuals including increased parenting stress and decreased access to mental health treatment. Among those reporting violence, Hispanic children and children with less externalizing problems were more likely to be in the discordant group. Findings suggest that both parent and child reports are needed to assess violence and screen for appropriate services.